A prehospital scoring system for predicting the need for emergent blood product transfusion. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Avital, Guy; Gelikas, Shaul; Radomislensky, Irina; Tsur, Avishai M.; Sorkin, Alex; Shinar, Eilat; Bodas, Moran; Yazer, Mark H.; Cap, Andrew P.; Chen, Jacob; Glassberg, Elon; Benov, Avi
Abstract: Background: Several tools have been proven to predict the need for massive transfusion in trauma casualties, yet tools that are easily applicable in the prehospital setting for predicting the need for any blood product transfusion in the emergency department (ED) are lacking. Methods: A retrospective analysis of the cross‐referenced Israeli Defense Forces Trauma Registry and the Israeli National Trauma Registry databases was performed to identify predictors for any blood product transfusion in the ED. A scoring system was developed after internally validating the prediction model. Division to risk groups was performed. Results: Seven variables (systolic blood pressure, heart rate, arterial oxygen saturation, trunk involvement, mechanism of injury, chest decompression, and tourniquet application) were included in the scoring system, ranging from 0 to 11.5. Risk groups for ED transfusion included very low (0.8%), low (3.2%), intermediate (8.5%), and high (31.2%) risk. Conclusion: A scoring system for predicting the need for any blood product transfusion in the ED was developed, based on information readily available in the early stages of prehospital resuscitation, allowing the receiving medical facility to prepare for that need.